Mapping of Civil Society Organizations in Uganda - Muhangi, Denis (UPHOLD CSO, 2004)
This report discusses the results of the Phase I study to map Civil Society Organizations (CSOs) in the 20 districts of Uganda, where UPHOLD is operating. Phase I was based on a review of secondary data both at national and district levels, as well as interviews with selected key informants at national level.The study focused on CSOs involved in the UPHOLD target sectors of Health, education, and HIV/AIDS, as well as the cross-cutting areas of gender, advocacy, capacity building, management, and communication. At national level, documentation of CSOs exists in form of directories and inventories compiled by different organizations. Most such compilations have been made by NGO network organizations including DENIVA, the National NGO Forum, HURRINET, and UNASO. Some NGOs and government programmes have also compiled directories to serve their needs. The NGO Registration Board in the Ministry of Internal Affairs has a listing of all organizations registered with it. The level and quality of documentation of CSOs at district level varies across districts. Some districts such as Pallisa and Gulu, through their Community Development Department or the District NGO Forum have directories of CSOs. Others (Lira, Bushenyi, Bundibugyo, Mbarara and Rukungiri) are in the process of recording CSOs. Yet others do not have any systematic or comprehensive record of their CSOs. The study results indicate that a very big number of CSOs exists in the districts, a listing by this study revealing 3,400 CSOs in the 20 districts. Yet this figure does not represent the actual number of CSOs that exist, but rather, only those captured in the documents that were accessed. The South-Western district of Bushenyi, Rukungiri and Mbarara revealed the biggest number of CSOs, while the Northern and North Eastern districts had the least number. Bushenyi had 1,160 CSOs, being the district with the biggest number of CSOs recorded. Districts that have been registering CBOs through their Community Development Departments reveal a very big number of CBOs. In almost all districts, CBOs were the most dominant type of CSOs that exists. International NGOs were mainly found in districts that have a history of civil war and other forms of conflict (Gulu, Kitgum, Nakapirirpirit, Bundibugyo, Luwero), and those with a history of other calamities such as HIV/AIDS (Rakai). Several of the CSOs could not be classified in terms of their type, due to unavailability of such information.